Participation of women in agricultural development programmes under people`s plan in Thiruvananthapuram district - Parvathy S (Department of Agricultural Extension, College of Agriculture, 2000)
The study entitled Participation of women in Agricultural Development Programmes under People's Plan in Thiruvananthapuram district was undertaken to study the extent of participation of women in planning implementation, monitoring and evaluation of Agriculture Development Programmes in People's Plan, perception of women about People's Plan campaign attitude of women towards People's Plan programme and and to identify the constraints as perceived by women and women office bearers while undertaking this programme. The study was conducted in eight grama panchayath of Thiruvananthapuram district selected randomly. A sample of two hundred respondents were selected using a mu l t i s t ag e random sampling. Data were collected through well structured and pretested interview schedule. Majority of rural women (64.37%) had medium extent of participation in planning while 67.57 per cent office bearers had high participation in planning. Great majority of rural women (98.7%) were low in their participation in implementing and majority (67.50%) of women office bearers were in high participation category. Around fifty two per cent of rural women having low level of participation in monitoring and evaluation while